Nosogenies in patients with myopia: clinical and psychological features - Drozdov , Volodymyr (The Ukrainian Scientific Medical Youth Journal, 2025)
nosogenies, as a category of the International Classification of Diseases, define distress or emotional disorder that interferes with a person’s social functioning and occurs in the presence of significant stress (or disease). The aim of the work was to determine the prevalence, clinical and psychological features of nosogenies in myopia. Affective disorders (mood disorders) were detected in 20.5% of people with myopia: mild depressive episode (9.0%), dysthymia (11.5%); in 65% – neurotic disorders related to stress and somatoform disorders: mixed anxiety-depressive disorder (11.0%), neurasthenia (55.5%), hypochondriac disorder (11.0%); in 2.0% – persistent personality changes not related to brain damage or disease: other persistent personality changes (2.0%). To study the personality characteristics of patients with myopia, we used the “Methodology of Multifaceted Personality Research. The study was conducted in accordance with the principles of the Declaration of Helsinki of the World Medical Association. Mathematical processing of the study results was performed using mathematical statistics methods. It was found that individuals with affective disorders were characterized by hypochondria, significant attention to their own health, impulsive behavior, anxiety, insecurity, difficulties in interpersonal interaction, and a focus on the world of internal experiences. Patients with myopia and neurotic disorders were characterized by a focus on their own health, lability and emotional instability, affective rigidity, lack of caution and prudence in actions, optimism, an active life position, high self-esteem, and a sufficient level of sociability. Patients with myopia and personality changes were characterized by pessimism, a tendency to introversion and skepticism, impulsiveness and uncontrolled behavior, individualism, originality of interests, and a decrease in general activity.